Penyusunan Laporan Keuangan di SMK Muhammadiyah 08 Medan - Teuku Radhifan Syauqi; Destari Nurlaila Damanik; Hanif Ramadhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the process of preparing financial reports at SMK Muhammadiyah 08 Medan, especially in trading businesses (UD), which is one form of SME economic unit. Trading businesses have the main characteristic of purchasing goods for resale without changing the nature of the goods, so that the preparation of accurate financial reports is very important to support business planning and strategy. However, many SMEs in Indonesia still face difficulties in understanding and implementing accounting, considering it as complicated, time-consuming, and costly. As a result, financial management often relies only on the memory of the business owner without formal recording. This study was conducted using a qualitative descriptive method, collecting data through interviews, observations, and documentation studies of the process of preparing financial reports at SMK Muhammadiyah 08 Medan. This study also refers to the application of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) released by the Financial Accounting Standards Board of the Indonesian Institute of Accountants (DSAK IAI) in 2016. The results of the study indicate that most trading business actors in the environment do not fully understand the importance of preparing financial reports in accordance with standards. Factors of limited resources, lack of understanding, and the assumption that financial reports are not needed are the main obstacles. This study provides recommendations in the form of simple accounting training that can help business actors prepare financial reports in accordance with SAK EMKM. The implementation of this recommendation is expected to improve accountability, transparency, and overall financial management of trading businesses.